TRANSLATION OF UKRAINIAN CRIMINAL PENALTIES INTO POLISH - LITWIN, Katarzyna; RACHTAN, Łukasz (Comparative Legilinguistics, 2012)
The bonds between Ukraine and Poland, developing collaboration also within the framework of mutual legal assistance between justice departments cause growing demand for legal translations in the field of criminal law. The absence of legal dictionaries and academic papers about Ukrainian legal terminology and the system of penalties in Ukraine leads to difficulties connected with providing equivalents by comparing parallel texts of statutes of these two countries. This paper analyses twelve types of penalties, regulated by criminal law of Ukraine, in the context of translation problems encountered in Ukrainian-Polish translation of legal texts. After presenting a brief comparison of Ukrainian and Polish regulations in different fields of law, the authors discuss the problematic issues connected with translation of the Ukrainian names of penalties, and also provide recommendations how to translate those terms effectively.